Optical nonlinearity in silicon at mid-infrared wavelengths - Wang, Ting (2014)
We report the wavelength dependency of third-order nonlinearity and multi-photon absorption of silicon in the spectral range from 1.6 µm to 6 µm, including the nonlinear figure of merit.